Genetic basis for variation in the number of cephalic pores in a hybrid zone between closely related species of goby, Gymnogobius breunigii and Gymnogobius castaneus. (25th March 2021) - Kakioka, Ryo; Kume, Manabu; Ishikawa, Asano; Ansai, Satoshi; Hosoki, Takuya K; Yamasaki, Yo Y; Nagano, Atsushi J; Toyoda, Atsushi; Kitano, Jun
Abstract: Populations or species exploiting different habitats can differ in sensory perception as a result of divergent adaptation. In bony fish, the water current is perceived via neuromasts, the end organ of the lateral line system. Although fish in different habitats are known to vary in neuromasts, we know little about the genetic basis for such variation. Here, we investigate the genetic basis for variation in supraorbital neuromasts in a hybrid zone between the Japanese gobies Gymnogobius breunigii and Gymnogobius castaneus . The former has supraorbital canal neuromasts with six cephalic pores, whereas the latter has only superficial neuromasts with no canals or pores in the supraorbital region. Our genomic analysis showed that G. breunigii and G. castaneus occur mainly in the lower and mid/upper reaches, respectively. In a river in northern Japan, hybrids were found at the sites between the habitats of the two species. These hybrids exhibited anomalies of cephalic pores. Using this hybrid zone, we conducted genome-wide association studies and identified one locus significantly associated with the number of pores. Genomic cline analysis in the hybrid zone demonstrated that this locus exhibited a higher introgression rate compared with the genomic background, indicating the possibility of adaptive introgression.